Implementation of Dakwah Bil Hal Ornamental Fish Traders in Economic Empowerment in Sekip Village, Lubuk Pakam District, Deli Serdang Regency - Tasya Amelia Pane; Sahrul Sahrul; Ilham Mirzaya Putra (Jurma : Jurnal Program Mahasiswa Kreatif, 2023)
The purpose of this study was to describe the form of implementation of da'wah bil hal ornamental fish traders in economic empowerment in Sekip Village, Lubuk Pakam District, and to describe the inhibiting factors, and supporting factors for the implementation of da'wah bil hal ornamental fish traders in economic empowerment in Sekip Village, Lubuk Pakam District. This type of research is descriptive using a qualitative approach. The research informants consisted of three ornamental fish traders and three ornamental fish consumers. Data collection tools are carried out through the stages of observation, interviews (interviews), and documentation. Data analysis techniques used data reduction, data presentation, and conclusion drawing. Based on the results of the study it was found that the form of implementation of da'wah bil hal ornamental fish traders in economic empowerment in Sekip Village, Lubuk Pakam District as follows: not reducing weight, selling good quality goods, being responsible for the quality of goods, promotion, loose and generous. Researchers also found the obstacles faced by ornamental fish traders in Sekip Village in trading, including factors of unpreparedness to compete, factors of lack of motivation, and factors of limited capital. Supporting factors include: increasing income and giving alms.